The Ethics of Financial Incentivization for Health Research Participation Among Sex Workers in a Canadian Context. (May 2022) - Bungay, Vicky; Guta, Adrian; Slemon, Allie; Varcoe, Colleen; Comber, Scott
Research incentivization with sex workers is common, yet limited guidance exists for ethical incentives practice. We undertook a critical qualitative inquiry into how researchers ( n = 17), community services staff ( n = 17), and sex workers participating in research ( n = 53) perceive incentives in a Canadian context. We employed an interpretive thematic approach informed by critical perspectives of relational autonomy for analysis. Four themes illustrate how (un)ethical use of incentives is situated in transactional micro-economies among groups experiencing severe marginalization: i) transactional research economy, ii) incentive type: assumptions and effects, iii) incentive amount: too much too little?, and iv) resistance, trauma, and research-related harm . Paternalistic assumptions about capacities of sex workers to act in their own best interests conflicted with participants' rights and abilities for self-determination; with researchers maintaining ultimate decision-making authority. Power differentials create conditions of harm. Safe, equitable approaches concerning research incentive use must redress relations of power that perpetuate oppression.